2015
DOI: 10.1016/j.jpainsymman.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Depressive Symptoms and Age in Cancer Patients: A Multicenter Cross-Sectional Study

Abstract: The finding that depressive symptoms in cancer patients decreased with age was concordant with our first hypothesis, but the second hypothesis was not supported. Younger cancer patients were vulnerable to depressive symptoms and should be monitored carefully. Further studies using more representative samples are needed to examine in detail the association between depressive symptoms and age in older cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
(42 reference statements)
2
8
0
1
Order By: Relevance
“…These results are consistent with previous research demonstrating that younger individuals experience more distress throughout the cancer experience (Wada et al, 2015) and that smoking places individuals at risk for compromised health (Duffy et al, 2007; Llewellyn, McGurk, & Weinman, 2005). Results are also in line with research showing that cancer-related symptoms play a major role in well-being; one study observed that HNC patient but not caregiver distress was worse when patients had poorer functioning (Verdonck-de Leeuw et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous research demonstrating that younger individuals experience more distress throughout the cancer experience (Wada et al, 2015) and that smoking places individuals at risk for compromised health (Duffy et al, 2007; Llewellyn, McGurk, & Weinman, 2005). Results are also in line with research showing that cancer-related symptoms play a major role in well-being; one study observed that HNC patient but not caregiver distress was worse when patients had poorer functioning (Verdonck-de Leeuw et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…While age, gender, and years of education are non-modifiable demographic characteristics, they are easily identifiable risk factors. Consistent with prior reports,[8,40,41] younger age was associated with higher fatigue severity. Potential explanations for this association may include: older patients being given lower doses of CTX;[42] age-related changes that modify inflammatory responses;[43] or a “response shift” in the symptom perceptions of older patients.…”
Section: Discussionsupporting
confidence: 92%
“…The timing of screening of psychological distress should be taken into account, as one year from the cancer diagnosis seems to be a time period, when patients cope better with distress, but shortly after treatment ends, distress level has been suggested to rise . As young cancer patients are suggested to be especially vulnerable to depressive symptoms, they should be monitored carefully . We did not find any clear difference in the magnitude of the risk for AD purchases within one year from cancer diagnosis compared to the time after one year from diagnosis.…”
Section: Discussionmentioning
confidence: 77%